[Sea Cliff on Heimaey From Boat] - Streng, Evelyn Fiedler (1975)
Photograph of a sea cliff on Heimaey from a boat. The grey and green cliff is covered in jagged edges and green grass. The cliff covers the photograph and sits along dark water at the bottom of the photograph. The white sky peeks through the rock at the top of the photograph.